How do inside directors affect corporate R&D investment? The moderating role of CEO equity incentives - Jianqing Zhou; Yulian Peng (PLoS ONE, 2025)
This study aims to reveal whether non-CEO inside directors can promote corporate research and development (R&D) investment. Using a panel data of 3,002 Chinese manufacturing listed firms from 2011 to 2021, we find that inside directors can significantly promote corporate R&D investment. We also find that when the CEO has equity incentives to alleviate agency conflicts, the role of inside directors in promoting R&D investment is significantly weakened. Additional analysis show that the promotive effect of inside directors on R&D investment is significant only in samples of non-state-owned enterprises (non-SOEs), male CEOs, older CEOs, and small boards, but not for the samples of state-owned enterprises (SOEs), female CEOs, younger CEOs, and large boards. These findings extend the scope of research on the economic consequences of inside directors and have important implications for the optimization and adjustment of corporate governance policies.